Pengaruh Free cash flow, Kepemilikan Institusional, Profitabilitas dan Leverage Tehadap Kebijakan Dividen Tunai Pada Perusahaan Property dan Real estate yang Terdaftar di Bursa Efek Indonesia - Syelly Wulandari; Nita Priska Ambarita; Mia Dwi Puji Wahyuni Darsono (Universitas Muhammadiyah Metro, 2019)
This research aims to examine and analyze the effect of free cash flow, institutional ownership, profitability and Leverage on dividend policy by using an approach multiple regression model. The proxies used to measure the financial elements are free cash flow, institutional ownership, Return on Assets and debt to equity ratio. The population in this research is property and real estate companies listed in Indonesia Stock Exchange for six years (2014-2019). Election sample procedure uses purposive sampling and the result are existed 5 companies that fulfill criteria so that amount of data studied by 30 data. The results of this research show that free cash flow, institutional ownership and profitability have a significant effect on dividend policy proxied by Dividend payout ratio. Leverage which is measured by debt to equity ratio hasn’t a significant effect on dividend policy. Free cash flow has a positive effect on dividend policy. Institutional ownership has a positive effect on dividend policy. Profitability which is measured by Return on Assets has a negative effect on dividend policy. The predictive ability of these variabel on dividend policy is 49,6% as shown by the amount of R square, while 50,4% is affected by the other factor which is not included in the research model.